Appraisal System Analysis in News Text "Prabowo-Gibran's Free Nutritious Meal Program Can Create New Jobs" (Functional Linguistic Systemic Study) - Ning Imas Ati Zuhrotul Afifah; Aya Said Mahmoud Said (Jurnal Sastra Indonesia, 2026)
This study aims to identify and analyze the appraisal system in the news text entitled “Prabowo-Gibran’s Free Nutritious Meal Program Can Create New Jobs” published by the digital news portal Liputan 6. The study is grounded in Systemic Functional Linguistics, particularly the appraisal framework, which examines how language constructs evaluative meanings, ideological positions, and interpersonal relations between writers and readers. Using a qualitative descriptive method, this research focuses on linguistic units in the form of words, phrases, and clauses that contain evaluative meanings related to affect, judgment, and appreciation. The data were collected through document analysis by carefully reading the news text, identifying clauses containing appraisal elements, coding them based on appraisal categories, and interpreting their evaluative tendencies. The findings show that the news text is dominated by positive appraisal resources. Affect is realized through expressions of hope, optimism, confidence, and expectation toward the implementation of the Free Nutritious Meal Program. Judgment appears mainly in the form of capacity, portraying the program as capable of generating economic benefits, creating employment opportunities, and strengthening rural communities. Appreciation is expressed through positive evaluation and institutional support, especially by emphasizing the usefulness, feasibility, and legitimacy of the program. These findings indicate that the news writer does not merely present information neutrally but also constructs a supportive and persuasive discourse. The text positions the MBG program as a beneficial public policy and implicitly functions as a soft campaign discourse that shapes readers’ positive perception and strengthens policy legitimacy. This study confirms that appraisal analysis is useful for revealing ideological tendencies in news discourse.